The Lateral Knee Radiograph: A Detailed Review - Kong, Andrew P.; Robbins, Robert M.; Stensby, James D.; Wissman, Robert D. (The Journal of Knee Surgery, 2022)
Initial imaging evaluation for a variety of knee pathologies often begins with a radiographic series. Depending on the specific indication, this will include at least two different projections of the knee. In most cases, these are the anteroposterior and lateral radiographs of the affected knee, and sometimes with the contralateral knee for comparison. Typically, knee pathologies visible on lateral view can also be appreciated on the anteroposterior view. However, several pathologic processes occur in anatomic locations typically obscured on other projections because of superimposed osseous structures. Examples of these pathologies include injuries involving the quadriceps or patellar tendons, avulsion fractures involving anterior or posterior structures, and many soft-tissue injuries. Knowledge of the relevant anatomy and typical pathologies typically visualized on the lateral radiograph of the knee is imperative to avoid overlooking these disease processes.
Keywords: lateral knee radiograph; lateral knee anatomy; extensor mechanism injury; avulsion injuries of the knee; fractures of the knee